Changes in prenatal testing during the COVID-19 pandemic - Handley, Sara C.; Ledyard, Rachel; Lundsberg, Lisbet S.; Passarella, Molly; Yang, Nancy; Son, Moeun; McKenney, Kathryn; Greenspan, Jay; Dysart, Kevin; Culhane, Jennifer F.; Burris, Heather H. (Frontiers in Pediatrics, 2022)
Objective The coronavirus disease 2019 (COVID-19) pandemic disrupted healthcare delivery, including prenatal care. The study objective was to assess if timing of routine prenatal testing changed during the COVID-19 pandemic. Methods Retrospective observational cohort study using claims data from a regional insurer (Highmark) and electronic health record data from two academic health systems (Penn Medicine and Yale New Haven) to compare prenatal testing timing in the pre-pandemic (03/10/2018–12/31/2018 and 03/10/2019–12/31/2019) and early COVID-19 pandemic (03/10/2020–12/31/2020) periods. Primary outcomes were second trimester fetal anatomy ultrasounds and gestational diabetes (GDM) testing. A secondary analysis examined first trimester ultrasounds. Results The three datasets included 31,474 pregnant patients. Mean gestational age for second trimester anatomy ultrasounds increased from the pre-pandemic to COVID-19 period (Highmark 19.4 vs. 19.6 weeks; Penn: 20.1 vs. 20.4 weeks; Yale: 18.8 vs. 19.2 weeks, all p < 0.001). There was a detectable decrease in the proportion of patients who completed the anatomy survey <20 weeks' gestation across datasets, which did not persist at <23 weeks' gestation. There were no consistent changes in timing of GDM screening. There were significant reductions in the proportion of patients with first trimester ultrasounds in the academic institutions (Penn: 57.7% vs. 40.6% and Yale: 78.7% vs. 65.5%, both p < 0.001) but not Highmark. Findings were similar with multivariable adjustment. Conclusion While some prenatal testing happened later in pregnancy during the pandemic, pregnant patients continued to receive appropriately timed testing. Despite disruptions in care delivery, prenatal screening remained a priority for patients and providers during the COVID-19 pandemic.